2020
DOI: 10.32457/ijmss.v7i2.503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera Lam. Leaf Extract Against Aluminium Chloride Induced Hippocampal Histology and Serum Enzyme activities in adult Wistar rats

Abstract: Introduction: Aluminium, a ubiquitous metal implicated in some neurodegenerative diseases is linked to activation of free oxygen species. The antioxidant-rich plants, Moringa oleifera (MO) is reported to protect against Aluminium activities. This study investigated the actions of MO leaf extract (MOLE) against Aluminium chloride (AlCl3 )- induced hippocampal cellular changes and serum levels of alkaline phosphatase (ALP), aspartate transaminase (AST) and alanine transaminase (ALT) in adult Wistar rats. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Some studies have confirmed that Moringa oleifera has a neuroprotective effect [84][85][86][87][88]; as far as we know, nevertheless, no studies have yet described and determined the potential effective neuroprotection components. Quercetin and kaempferol derivatives are the main polyphenols in Moringa oleifera leaves.…”
Section: Effect Of Polyphenols In Mlpe Against H 2 O 2 -Induced Oxidative Stress In Pc-12 Neuroblastoma Cellsmentioning
confidence: 99%
“…Some studies have confirmed that Moringa oleifera has a neuroprotective effect [84][85][86][87][88]; as far as we know, nevertheless, no studies have yet described and determined the potential effective neuroprotection components. Quercetin and kaempferol derivatives are the main polyphenols in Moringa oleifera leaves.…”
Section: Effect Of Polyphenols In Mlpe Against H 2 O 2 -Induced Oxidative Stress In Pc-12 Neuroblastoma Cellsmentioning
confidence: 99%
“…The remaining forty-eight mice were equally divided into eight groups (n = 6), and were orally administered AlCl 3 at 100 mg/kg body weight (Ekong et al 2017;Adighije et al 2020), and Z. officinale ethanol, dichloromethane (DCM), and methanol extracts daily for 21 days: Group 1 were the control administered 40 mL/kg of distilled water daily; group 2 were administered 100 mg/kg AlCl 3 only; group 3 were concurrently administered 100 mg/kg AlCl 3 and 2.5 mg/kg of donepezil; while groups 4-6 were concurrently administered 100 mg/kg AlCl 3 and 474 mg/kg (10% LD 50 low dose), 949 mg/kg (20% LD 50 intermediate dose), and 1,423 mg/kg (30% LD 50 high dose) Z. officinale ethanol extract; groups 7 and 8 were concurrently administered 100 mg/kg AlCl 3 and 949 mg/kg DCM or 949 mg/kg methanol fractions of Z. officinale.…”
Section: Animal Handling and Groupingmentioning
confidence: 99%